Nonlinear BER performance of dense optical WDM manhattan street network with deflection routing - Hiew, C. C.; Abbou, F. M.; Chuah, Hean Teik; Majumder, Satya Prasad; Abdul Rashid, Hairul Azhar (IEEE, 2006)
The nonlinear bit-error-rate (BER) performance of dense optical wavelength-division-multiplexed (WDM) Manhattan Street Networks with deflection routing was evaluated using an extendable semianalytical process. The results show that nonlinear effects impose significant performance penalties on dense WDM networks, both in terms of maximum hops attainable and average BER, and should be taken into account when modeling such networks. Simple techniques such as optimal amplifier positioning can reduce the nonlinear penalties.